Skład środowiska robotników przemysłowych Krakowa w okresie 1945-1956 - Chumiński, Jędrzej (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
To reconstruct the state of social awareness of the workers in the early years of the People's Republic of Poland, the forms of coexistence with the system, the extent of the social resistance in the decades to follow, one cannot proceed without the regard to the vital changes that had occured as far as the structure of the class is concerned. Casualties, war and post-war migration, recruitment of people from other social groups for the word in industry, were the basic reasons why the integration of the workers' communities proved to be so difficult. Even thought the working conditions and the financial situation were very much alike after 1945, the workers themselves differed with regard to the social origin, professional experience, level of education, outlook on life or politics, moral standards, internalization of traditional working class values. In the article the author presents the process of moulding the industrial workers en environment in the city Cracow. In Cracow the social class of workers had not been destroyed during the Second War and because of that, defeating and désintégration of prewar society of workers was much lee that in other regions of Poland. It had crucial influence on workers attitudes and behaviours. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Nauki Humanistyczne (10); 2006; nr 1149, s. 109-134